2020
DOI: 10.3390/jcm9103096
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Antibacterial Properties of Novel, Premixed Calcium Silicate-Based Sealer Compared to Powder–Liquid Bioceramic Sealer

Abstract: The aim of this study was to compare the physicochemical properties, filling ability, and antibacterial activity of a premixed calcium silicate-based sealer to those of a powder–liquid bioceramic sealer. Ceraseal (CS) and BioRoot (BR) materials were analyzed using scanning electron microscopy and energy-dispersive X-ray spectroscopy at 7 and 14 d of immersion in distilled water. The filling ability of the two sealers as well as the water contact angle, solubility, flow, roughness, crystalline microstructure, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(134 citation statements)
references
References 61 publications
7
121
1
5
Order By: Relevance
“…BioRoot TM RCS (Colombo et al, 2018;Kharouf et al, 2020) and TotalFill BC sealer (Colombo et al, 2018) exhibited high alkaline pH (up to 11) at 24 hours, similar to the previous studies on EndoSequence BC Sealer, EndoSeal MTA and MTA Fillapex (Lee et al, 2017). High alkalinity of EndoSeal MTA (Lim et al, 2015) and CeraSeal Bioceramic root canal sealer (Kharouf et al, 2020) have also been reported.…”
Section: Ph Valuessupporting
confidence: 86%
See 3 more Smart Citations
“…BioRoot TM RCS (Colombo et al, 2018;Kharouf et al, 2020) and TotalFill BC sealer (Colombo et al, 2018) exhibited high alkaline pH (up to 11) at 24 hours, similar to the previous studies on EndoSequence BC Sealer, EndoSeal MTA and MTA Fillapex (Lee et al, 2017). High alkalinity of EndoSeal MTA (Lim et al, 2015) and CeraSeal Bioceramic root canal sealer (Kharouf et al, 2020) have also been reported.…”
Section: Ph Valuessupporting
confidence: 86%
“…This includes setting time, flowability, solubility, radiopacity, film thickness, and dimensional stability. Some studies on the physicochemical properties of bioceramic root canal sealers have been conducted according to these specifications (Vidotto et al, 2011;Borges et al, 2014;Camargo et al, 2017;Lee et al, 2017;Poggio et al, 2017;Colombo et al, 2018;Khalil et al, 2019), although other researchers have used the International Organisation for Standardisation (ISO) 6876 specifications (Gandolfi and Prati, 2010;de Miranda Candeiro et al, 2012;Vitti et al, 2013;Zhou et al, 2013;Lim et al, 2015;Agarwal and Nikhil, 2016;Lee et al, 2017;Poggio et al, 2017;Tanomaru-Filho et al, 2017;Colombo et al, 2018;Mendes et al, 2018;Zordan-Bronzel et al, 2019;Kharouf et al, 2020). The ASTM standards C266-07 and C373-88 have also been used to evaluate the setting time and solubility respectively (Gandolfi and Prati, 2010).…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The agar diffusion tests were performed as described in a previous study [ 32 ]. Three agar-filled Petri dishes containing 25 mL of BHI agar were used.…”
Section: Methodsmentioning
confidence: 99%